Konsep Pemenuhan Hak Atas Pangan Bagi Masyarakat Di Wilayah Perbatasan Pada Masa Pandemi Covid-19 - Yusran Baginda Luhulima; Josina Augustina Yvonne Wattimena; Johanis Steny Franco Peilouw (Pattimura Legal Journal)
Introduction: The right to food is a very important right to fulfill, because without food, the survival and welfare of society cannot be realized.